Gender differences in the impact of 3-year status changes of metabolic syndrome and its components on incident type 2 diabetes mellitus: a decade of follow-up in the Tehran Lipid and Glucose Study - Hadaegh, Farzad; Abdi, Amir; Kohansal, Karim; Hadaegh, Parto; Azizi, Fereidoun; Tohidi, Maryam (Frontiers in Endocrinology, 2023)
Background: To examine the gender differences in the association between status changes of metabolic syndrome (MetS) and its components, using Joint Interim Statement (JIS) criteria, with the risk of type 2 diabetes mellitus (T2DM) among an urban population. Methods: The study included 4463 Iranian adult participants (2549 women) aged ≥ 20 years. Based on status changes of MetS and its components during three years, subjects were categorized into four groups: MetS-free (reference), MetS-developed, MetS-recovery, and MetS-stable. A similar categorization was applied to MetS components. Multivariable Cox regression models were used for estimating hazard ratios (HRs), women-to-men ratios of HRs (RHRs). Results: During a median follow-up of 9.3 years, 625 T2DM events (351 women) occurred. Compared with the reference, the HRs of the MetS-developed, -recovery, and -stable groups among men for incident T2DM were 2.90, 2.60, and 4.92; the corresponding values for women were 2.73, 2.88, and 5.21, respectively (all p-values < 0.01), without significant gender difference in these relationships. In both genders, the fasting plasma glucose (FPG) component, regardless of the change in status, was strongly and significantly associated with incident T2DM with HRs ranging from 2.49 to 9.42; a similar association was also found for high waist circumference (WC)-recovery and –stable groups, with HRs ranging from 1.58 to 2.85 (p-values ≤ 0.05). Regarding gender differences, the development and persistence of high blood pressure (BP) status exposed men to greater T2DM risk than women with women-to-men RHRs of 0.43 (0.26-0.72) and 0.58 (0.39-0.86), respectively. Moreover, stable low levels of high-density lipoprotein cholesterol (HDL-C) and high triglycerides (TG) levels conferred higher T2DM risk in women than men, with women-to-men RHRs of 1.67 (0.98-2.86) and 1.44 (0.98-2.14), respectively (both p-values=0.06). Conclusions: Among Tehranian adults, in both genders, all status changes of MetS, even those recovered from MetS, have a higher risk of T2DM compared to those who never had MetS. Also, all statuses of high FPG, in addition to recovered and stable high WC, were strongly associated with T2DM risk. Specifically, men with stable or developed high BP and women with stable dyslipidemic status were at differentially increased risk of incident T2DM.